Internal structure of verb meaning: A study of verbs of (change of) state in Tamazight (Berber) - Achab, Karim (University of Ottawa (Canada), 2006)
The dissertation investigates verbs of (change of) state in Tamazight (Berber) from the perspective of their internal structure and its syntactic corollary, which corresponds to predicate-argument structure. The verbs investigated include verbs of quality, unaccusatives, spatial configuration verbs, and causatives. Verbs of quality refer to a special class of intransitive verbs occurring with accusative clitics when they indicate a pure state, and with nominative clitics when they indicate change of state. In the latter situation verbs of quality are undistinguished from unaccusatives. I argue that while nominative clitics associated with verbs of quality surface in the subject position for EPP reasons, accusative clitics surfaces in the object position because the category T involved is defective, following an idea proposed by Chomsky (2001). This contradicts the view in Government and Binding Theory that intransitive verbs do not assign unaccusative Case. I sustain that the pure state form has a monadic structure of the type [VBE[√ROOT]], while the inchoative form, like unaccusatives, is associated with the dyadic structure of the type [VCOME[V BE[√ROOT]]]. To account for the two different interpretations associated with the inchoative form I argue that its syntactic structure contains a scope operator with two different positions. When the operator has scope over VCOME, it yields change of state interpretation; when the operator has scope over VBE, the interpretation is stative (resultative). Verbs of quality and unaccusatives are contrasted with verbs of spatial configuration which are analyzed as disguised reflexives, with a triadic structure of the type [VACT[VCOME[VBE([√ROOT])]]]. The reflexive interpretation results from the association of the internal argument with two thematic positions [Spec,VACT] and [Spec,V COME]. The structure postulated for causatives is of the type [VCAUSE [COME[VBE([√ROOT])]]]. I argue that lexical causatives have a basic structure while morphological causatives are derived by augmenting their unaccusative counterpart. Lexical causatives are of two types. I argue that those lacking the unaccusative alternate have their lexical root conflated with the verb CAUSE, while unaccusative-alternating causatives have their lexical root conflated with the lower verbs (BE)COME. This idea is extended to account for the difference between unaccusative-alternating and non-alternating languages.
Keywords: Language, Linguistics.